Design of a Tri-Band Antenna Microstrip for a Wban the Low Sar [Diseño de Una Antena Microstrip de Tres Bandas Para Una Wban de Bajo Sar] - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents a new design of a Tri-band microstrip antenna for a WBAN (Wireless Body Area Network) low SAR (Specific Absorption Rate). The proposed antenna consists of L-shaped slots have been determined based on the frequency bands. For the integration of these techniques three frequency bands consisting of the ISM band 2.4 GHz and 5.7 GHz, and 3.5 GHz band UWB respectively were considered. The proposed antenna is designed with the purpose of obtaining a low SAR models of the human body, considering both the electromagnetic effect and the shell model in human tissues. © 2016 IEEE.